Pengaruh Program Samsat Kerti, Sanksi Pajak, Dan Sosialisasi Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Studi Kasus Di Kantor Bersama Samsat Jembrana) - Made Deva Aditya Fernanda; I Nyoman Putra Yasa (Universitas Pendidikan Ganesha, 2021)
This research was conducted with the aim to know the influence of Samsat Kerti program, tax penalties, and tax sosialization toward motor vehicles taxpayers compliance in Jembrana Regency. This research is classified as a quantitative study, where primary data is the kind of data used in this research. Primary data were collected by distributing questionnaires directly and online via Google Form. Population of this resesarch are motor vehicle taxpayers that registered in Jembrana Samsat Office which amounts to 11.924 taxpayers. The sampling technique applied is purposive random sampling technique. Then the sample determined were 130 respondents, which is a motor vehicle taxpayer who is domicilied in Jembrana Regency and have been used services of Samsat Kerti. The techniques used in analyzing the data, started from testing of data quality, descriptive analysis, classic assumption tests, multiple linear regression analysis, until t tests, and the coefficient of determination (R2) by using SPSS version 24.0 for windows. This research obtained the result that each variables Samsat Kerti program (X1), tax penalties (X2), and tax sosialization (X3) have positive and significant influence toward motor vehicle taxpayers compliance (Y).